THE ENHANCEMENT OF GIVING REASON AND GIVING HYPOTESIS ALSO MAKING DEFINITION IN CHEMISTRY BY SSCS LEARNING MODEL - khususiyah khususiyah; chansyanah diawati; nina kadaritna (Universitas Lampung, 2012)
The objective of this research is to describe the learning model of SSCS that effective to improve the students’ ability in giving reason, giving hypotesis and making definition. This research used quasi experiment method with Nonequivalent Control Group Design . The Samples of this research were the second year students of MAN 1 Bandar Lampung in the even of academic year 2011-2012. The research used two classes, XI IPA2 and X IPA3which had the same characteristic. The effectiveness of SSCS the learning model was measured by differences of significant n-gain. The results of this research showed that the mean value of n-gain for students’ ability in giving reason in control and experiment class were -0,04 and 0,45; the mean value of n-gain for students’ ability in giving hypotesis in control and experiment class were -0,03 and 0,32; and the mean value of n-gain for students’ ability in making definition in control experiment class were -0,26 and 0,40. Based on hypotesis test, it can be seen that the SSCS learning model is effective to improve the student’ ability in giving reason, giving hypotesis and making definition.Keywords: SSCS learning model, students’ ability in giving reason, giving hypotesis and making definition.